Online patient endoscopy education platform improves outpatient bowel preparation quality: Retrospective observational study - Ding, Yuming; Vandeleur, Ann; Chinchilla, Gonzalo; Littlemore, Kimberley; Hodgson, Ruth; Rahman, Tony (Endoscopy International Open, 2024)
Background and study aims High-quality bowel preparation is integral to high-quality colonoscopy and adenoma detection. Studies evaluating the effect of pre-colonoscopy educational videos on bowel preparation quality have been variable. We investigated whether augmenting bowel preparation education using our professionally produced, patient-oriented, online educational video series would improve preparation quality, reduce need for repeat procedures, and improve adenoma detection rate (ADR).Patients and methods We conducted a pilot, retrospective, single-center observational study using endoscopy data from a tertiary hospital. Colonoscopy outcomes were compared between two discrete 6-month study periods, before (control group) and after (video group) implementation of the online video intervention. All patients received standard-of-care written and verbal instructions. The video group received a link providing access to the video platform. Primary outcome was adequacy of bowel preparation (defined by the Aronchick Scale). Secondary outcomes included rate of repeat colonoscopy due to inadequate preparation, ADR, and sessile serrated lesion (SSL) detection rate.Results The video intervention group had a lower rate of inadequate bowel preparation compared with the control group (6.3% vs 9.8%, P = 0.018). There was no difference between groups in rate of repeat colonoscopies due to inadequate preparation (P = 0.62), ADR (P = 0.11), or SSL detection rate (P = 0.94). Multivariable analysis did not reveal any independent predictors of bowel preparation quality.Conclusions Our study supports the addition of a novel patient-oriented online educational video resource as an effective tool in enhancing bowel preparation adequacy while maintaining provision of high-quality colonoscopy.
Keywords: Endoscopy Lower GI Tract; Colorectal cancer; Polyps/adenomas/...; CRC screening